Communication and the First World War
1 online resource (xiv, 310 pages)
Keywords: Despite the voluminous historical literature on the First World War, a volume devoted to the theme of communication has yet to appear. From the communication of war aims and objectives to the communication of war call-up and war experience and knowledge, this volume fills the gap in the market, including the work of both established and newly emerging scholars working on the First World War across the globe. The volume includes chapters that focus on the experience of belligerent and also neutral powers, thus providing a genuinely representative dimension to the subject.